Negative regulation of Schistosoma japonicum egg-induced liver fibrosis by natural killer cells. - Xin Hou; Fazhi Yu; Suqin Man; Dake Huang; Yuxia Zhang; Miao Liu; Cuiping Ren; Jijia Shen (Public Library of Science (PLoS), 2012)
The role of natural killer (NK) cells in infection-induced liver fibrosis remains obscure. In this study, we elucidated the effect of NK cells on Schistosoma japonicum (S. japonicum) egg-induced liver fibrosis. Liver fibrosis was induced by infecting C57BL/6 mice with 18-20 cercariae of S. japonicum. Anti-ASGM1 antibody was used to deplete NK cells. Toll-like receptor 3 ligand, polyinosinic-polycytidylic acid (poly I:C) was used to enhance the activation of NK cells. Results showed that NK cells were accumulated and activated after S. japonicum infection, as evidenced by the elevation of CD69 expression and IFN-γ production. Depletion of NK cells markedly enhanced S. japonicum egg-induced liver fibrosis. Administration of poly I:C further activated NK cells to produce IFN-γ and attenuated S. japonicum egg-induced liver fibrosis. The observed protective effect of poly I:C on liver fibrosis was diminished through depletion of NK cells. Disruption of IFN-γ gene enhanced liver fibrosis and partially abolished the suppression of liver fibrosis by poly I:C. Moreover, expression of retinoic acid early inducible 1 (RAE 1), the NKG2D ligand, was detectable at high levels on activated hepatic stellate cells derived from S. japonicum-infected mice, which made them more susceptible to hepatic NK cell killing. In conclusion, our findings suggest that the activated NK cells in the liver after S. japonicum infection negatively regulate egg-induced liver fibrosis via producing IFN-γ, and killing activated stellate cells.